The role of teaching methods in developing the abilities of mentally gifted students (Journal of the College of Basic Education, 2023)
Developed countries in the world are interested in caring for their mentally and skillfully gifted children, working to invest their capabilities on the largest scale in serving their societies economically, socially and culturally.Developing countries followed the example of developed countries, showing interest in educating some of their mentally outstanding children and their different characteristics, which enables them to provide appropriate educational care that achieves benefit from their capabilities. who can play this class .(Abdul Ghaffar, 1966, p. 19)Society may neglect some of these children while they can prove their presence in most cases, their activity is unusual and their behavior is distinct and usually receive rejection from those around them from friends, teachers and relatives, because some of them believe that these children should be stopped at their limits as they view their behavior as unacceptable. Reasonable or acceptable as they see them as eccentrics and sometimes they see them arrogant and do not consider the problems of others and unsociable and even undisciplined and that they must be deterred and treated with a kind of cruelty and firmness in order to learn how to behave in a normal and acceptable way, except that this method may extinguish in mentally superior students that luminous flame that if She received care to light the way for them, their families and their community.